2022
DOI: 10.1001/jamanetworkopen.2022.45510
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking, Comorbidity, Clinical Stage, and Treatment Intent With Socioeconomic Differences in Survival After Oropharyngeal Squamous Cell Carcinoma in Denmark

Abstract: ImportanceThe socioeconomic gap in survival after cancer is pronounced among patients with head and neck cancer. Understanding the mechanisms of this gap is crucial to target intervention strategies.ObjectiveTo investigate socioeconomic differences in survival after oropharyngeal squamous cell carcinoma (OPSCC) according to human papillomavirus (HPV) status and the extent to which smoking, comorbidity, clinical stage, and treatment intent explain the survival gap.Design, Setting, and ParticipantsThis nationwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These lifestyle choices also characterise people with a low SES who also often have low educational level, income, social status and occupational status (Halgren Olsen et al, 2019). Thus, it is well documented that the majority of patients with head and neck cancer have a low SES (Choi et al, 2016;Jakobsen et al, 2018); this increases the risk of inequality in the treatment of head and neck cancer, which has also been documented in several other studies (Andersen et al, 2008;Choi et al, 2016;Halgren Olsen et al, 2022). Lineback et al (2017) found that patients with oesophageal cancer with a low SES status were more likely to be offered less surgery than patients with a high SES (Lineback et al, 2017), which was also found for patients with head and neck cancer being offered radiation therapy as documented by Park and Decker (Park & Decker, 2016).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…These lifestyle choices also characterise people with a low SES who also often have low educational level, income, social status and occupational status (Halgren Olsen et al, 2019). Thus, it is well documented that the majority of patients with head and neck cancer have a low SES (Choi et al, 2016;Jakobsen et al, 2018); this increases the risk of inequality in the treatment of head and neck cancer, which has also been documented in several other studies (Andersen et al, 2008;Choi et al, 2016;Halgren Olsen et al, 2022). Lineback et al (2017) found that patients with oesophageal cancer with a low SES status were more likely to be offered less surgery than patients with a high SES (Lineback et al, 2017), which was also found for patients with head and neck cancer being offered radiation therapy as documented by Park and Decker (Park & Decker, 2016).…”
Section: Introductionmentioning
confidence: 71%
“…These lifestyle choices also characterise people with a low SES who also often have low educational level, income, social status and occupational status (Halgren Olsen et al, 2019). Thus, it is well documented that the majority of patients with head and neck cancer have a low SES (Choi et al, 2016; Jakobsen et al, 2018); this increases the risk of inequality in the treatment of head and neck cancer, which has also been documented in several other studies (Andersen et al, 2008; Choi et al, 2016; Halgren Olsen et al, 2022).…”
Section: Introductionmentioning
confidence: 71%
“…However, due to the complex anatomy of head and neck, it is difficult to perform surgery. When patients are diagnosed with head and neck cancer, more than 50% of them are in clinical stage III or IV and lose their best chance of operation [2]. This is one of the reasons why the total global survival rate of HNSCC is only 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, rural residents and people of black ethnicity have a higher incidence rate and a worse prognosis, which might be attributed to socioeconomic barriers such as insurance and income (5,6). As for educational attainment, a Danish study found that the incidence of oropharyngeal cancer increased in individuals with a short education (7), and a recent cohort study discovered that those with a lower educational level usually had a lower survival rate (8). However, these traditional observational results tend to be biased by undetectable potential confounders and should be explained with caution (9).…”
Section: Introductionmentioning
confidence: 99%